Predictors of failure and success of tibial interventions for critical limb ischemia - Fernandez, Nathan (2010)
OBJECTIVE: The efficacy of tibial artery endovascular intervention (TAEI) for critical limb ischemia (CLI) and particularly for wound healing is not fully defined. The purpose of this study is to determine predictors of failure and success for TAEI in the setting of CLI. METHODS: All TAEI for tissue loss or rest pain (Rutherford classes 4, 5, and 6) from 2004 to 2008 were retrospectively reviewed. Clinical outcomes and patency rates were analyzed by multivariable Cox proportional hazards regression and life table analysis. RESULTS: One hundred twenty-three limbs in 111 patients (62% male, mean age 74) were treated. Sixty-seven percent of patients were diabetics, 55% had renal insufficiency, and 21% required hemodialysis. One hundred two limbs (83%) exhibited tissue loss; all others had ischemic rest pain. All patients underwent tibial angioplasty (PTA). Tibial excimer laser atherectomy was performed in 14% of the patients. Interventions were performed on multiple tibial vessels in 20% of limbs. Isolated tibial procedures were performed on 50 limbs (41%), while 73 patients had concurrent ipsilateral superficial femoral artery or popliteal interventions. The mean distal popliteal and tibial runoff score improved from 11.8 ± 3.6 to 6.7 ± 1.6 (P < .001), and the mean ankle-brachial index increased from 0.61 ± 0.26 to 0.85 ± 0.22 (P < .001). Surgical bypass was required in seven patients (6%). The mean follow up was 6.8 ± 6.6 months, while the 1-year primary, primary-assisted, and secondary patency rates were 33%, 50%, and 56% respectively. Limb salvage rate at 1 year was 75%. Factors found to be associated with impaired limb salvage included renal insufficiency (hazard ratio [HR] = 5.7; P = .03) and the need for pedal intervention (HR = 13.75; P = .04). TAEI in an isolated peroneal artery (odds ratio = 7.80; P = .01) was associated with impaired wound healing, whereas multilevel intervention (HR = 2.1; P = .009) and tibial laser atherectomy (HR = 3.1; P = .01) were predictors of wound healing. In patients with tissue loss, 41% achieved complete closure (mean time to healing, 10.7 ± 7.4 months), and 39% exhibited partial wound healing (mean follow up, 4.4 ± 4.8 months) at last follow up. Diabetes, smoking, statin therapy, and revascularization of >1 tibial vessel had no impact on limb salvage or wound healing. Re-intervention rate was 50% at 1 year. CONCLUSIONS: TAEI is an effective treatment for CLI with acceptable limb salvage and wound healing rates, but requires a high rate of reintervention. Patients with renal failure, pedal disease, or isolated peroneal runoff have poor outcomes with TAEI and should be considered for surgical bypass. (J Vasc Surg 2010;52:834-42.)